Peningkatan Hasil Belajar Al-Qur’an Hadits Siswa Kelas XI dengan Metode PQ4R: Preview, Question, Read, Reflect, Recite, Review dan Tutor Sebaya di MA Darul Amanah Bedono Kabupaten Semarang - Adhel, Adhe Lia Anggreyani; Mustafidin, Ahmad; Maskur; Aliwan; Hendri Saputri, Belina (Lembaga Penelitian dan Pengabdian Masyarakat STAI Brebes, 2025)
Type your abstract here (10 pt). This study is a Classroom Action Research (CAR) prompted by the low learning outcomes of students in the Qur’an Hadith subject for Grade XI at MA Darul Amanah Bedono. The previous learning approach relied heavily on memorization, which led to students being less active, passive, and lacking deep engagement in the learning process. Initial data showed that only 2 out of 7 students (28.57%) met the Minimum Mastery Criteria (KKM), while the remaining students did not demonstrate adequate learning outcomes. To address this issue, classroom action was taken by implementing the Preview, Question, Read, Reflect, Recite, Review (PQ4R) method combined with a peer tutoring strategy, aiming to foster active involvement and deeper understanding among students. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. In the first cycle, there was a significant improvement in learning outcomes, with 4 out of 7 students (57.14%) meeting the KKM, and the class average rising to 73.28. Learning activities also improved, with the teacher activity score reaching 3.0 and the student activity score 2.8. In the second cycle, technological innovation was introduced by integrating Chromebook-based media to support the PQ4R and peer tutoring activities. As a result, 6 students (85.71%) achieved the KKM, and the activity scores increased to 3.8 for teachers and 3.6 for students. Data collection methods included observation, formative tests, interviews, and documentation. Observation was used to assess classroom dynamics and student participation. Tests were used to measure students' cognitive achievement, interviews explored student responses to the applied methods, and documentation provided supporting data. The data were analyzed quantitatively to measure improvements in learning outcomes and qualitatively to evaluate the learning process and changes in student behavior. The findings indicate that the combination of the PQ4R method and peer tutoring, supported by technological media, effectively improved student learning outcomes in the Qur’an Hadith subject—both cognitively and participatively. This approach may serve as an innovative alternative instructional model to enhance the quality of Islamic education learning at the senior high school level.